Electrical, Thermal Parameter Calculations of Artificially Removed Human Renal Stones by Two-Probes Method - SUNDARAMOORTHI, P.; KALAINATHAN, S.; KANCHANA, G.; SANTHI, R. (Asian Journal of Chemistry, 2010)
Electrical, thermal conductivity studies play a vital role in the field of science and technology. According to the conductivity terms, the world materials can be classified in to good conductors, bad conductors, semiconductors and super conductors. As per the free electron theory, the free electron only acts as carrier and carries their energy from one point to another point either natural or forced. In the present investigation, five renal stones were collected from the poor hard working males who are affected with mineral deposition in the urinary tracts. The stones were collected from the hospital by lithotropic treatment process. Using two-probes method, the electrical conductivity was measured at different temperatures. The thermal conductivity and temperature coefficients were calculated.